EVALUATION OF THERMAL COMFORT IN DAIRY CATTLE USING DATA MINING - PERISSINOTTO, MAURÍCIO; MOURA, DANIELLA J. DE (Revista Brasileira de Engenharia de Biossistemas, 2007)
Some studies had already had shown that the animal performance is influenced by thethermal environment and that the intensity that it occurs is function of the region that theanimals are lodged, questioning the limits of the temperature and humidity index (THI).The objective of this study was to model and to evaluate the impact of the thermal stressusing the Data Mining of meteorological data (air temperature and relative humidity) andphysiological data (rectal temperature and respiratory rate) and thus to determine thecritical intervals of the THI. The data base was built with meteorological and physiologicaldata from a commercial farm located in the city of São Pedro - SP. For the Data Miningprocess the computational program Weka was used, version 3-4, using the J48 algorithmto build a decision tree. According to the results it is possible to adapt the THI in functionof the region and the animals using the Data Mining of meteorological and physiologicaldata. The analysis of the data base indicated a high capacity of the model in representingthe classes of comfort from this data set. It was found that when the internal THI is loweror equal the 77 the thermal comfort is high, and when it is higher than 80 is low.